Dialogue on Health and Safety at Work: The Polish Experience and the Perspective of International Labour Law - Jarota, Maciej (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The dialogue between employers and trade unions in the OHS sphere is a key element in strengthening workers’ health protection. Many ILO Conventions and Recommendations refer to cooperation between employers and workers on working conditions. In view of the new OHS risks, OHS consultations with workers should be strengthened. Their support should consist in popularising this form of dialogue. In addition, the introduction in the Labour Code of tools ordering the proceedings before the OHS Commission may be justified especially from the perspective of the efficiency and substantive course of its meetings. Poland should also ratify ILO Conventions No. 155 and No. 187, which could give more importance to consultations on matters of health and safety at work.